A framework for information warehouse development processes - Roland Holten (Westfälische Wilhelms-Universität Münster, Institut für Wirtschaftsinformatik, 1999)
Since the terms Data Warehouse and On-Line Analytical Processing were proposed by Inmon and Codd, Codd, Sally respectively the traditional ideas of creating information systems in support of managements decision became interesting again in theory and practice. Today information warehousing is a strategic market for any data base systems vendor. Nevertheless the theoretical discussions of this topic go back to the early years of the 20th century as far as management science and accounting theory are concerned and to the late 50s and early 60s when focussing information systems aspects. Although today efficient technology is available to develop information systems for managements purposes information warehouse projects are still very risky and most of them are not finished successfully. The main reason for this situation lies in the lack of suitable languages to develop the conceptual specification of information warehouses. Based on this drawback methods for the development of information warehouses cannot be specified clearly. This paper proposes a language for the required conceptual specification of information warehouses based on an thorough analysis of management and accounting approaches to this topic and shows how this language can be integrated in a two dimensional development framework for information warehouse development as fundamental component.
Keywords: 650